Teaching & Learning Guide for: What Should Historians Do with Heroes?: Reflections on Nineteenth- and Twentieth-Century Britain - Jones, Max (History compass, 2007)
This article arose out of my development of undergraduate courses related to my research on national heroes. An effective course needs to encourage students to move beyond the narrow ‘debunking’ approach to heroes frequently adopted in popular biographies and television documentaries, and situate the heroes of the past in a broader historical context. Students should be asked why certain individuals were invested with special symbolic significance in the past? What forms this investment took? And how the forms and purposes of this investment changed over time? Geoffrey Cubitt's definition of a hero provided a useful starting-point, but first-year undergraduates found the essay in which Cubitt presented his definition challenging. I was therefore delighted to accept History Compass's invitation to write an introduction to the analysis of heroes aimed primarily at undergraduates. I also took the opportunity to identify what seemed to me to be a significant shift in scholarly approaches to heroes over the last thirty years, from an initial preoccupation with the function of heroes as tools of nationalist and imperialist ideologies, to broader analyses of the range of gendered meanings encoded in heroic reputations.